CORUNDUM+QUARTZ ASSOCIATION IN ARCHEAN GRANULITE-FACIES ROCK FROM ENDERBY LAND, EAST ANTARCTICA : PRELIMINARY INTERPRETATION - モトヨシ, ヨウイチ; マツエダ, ヒロハル; MOTOYOSHI, Yoichi; MATSUEDA, Hiroharu (National Institute of Polar Research, 1987)
P(論文) Corundum occurs in direct contact with quartz in a high-temperature granulite-facies metamorphosed quartzite from the Archean Napier Complex in Enderby Land, East Antarctica. The quartzite is composed dominantly of bluish-gray quartz with mesoperthitic K-feldspar and spinel as subordinate constituents. Corundum occurs always being interlocked with spinel and both minerals are in direct contact with quartz. Under the P-T conditions of the Napier granulites (900-1000℃, 7-10kbar), sillimanite should be a stable Al_2SiO_5,and corundum cannot coexist stably with quartz. On the basis of the petrographical evidence, the corundum is inferred to be an exsolved product from spinel solid solution upon cooling, and it did not react with surrounding quartz to form Al_2SiO_5 probably due to the high activation energy required for the solid-solid interaction between corundum and quartz. departmental bulletin paper